Sylwetki wojewodów tarnopolskich w II Rzeczypospolitej - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The Tarnopol province voivodeship was created only on 1 September 1921, after the controversy of Eastern Galicia’s nationality was resolved and when Polish-Ukrainian and Polish-Russian fighting came to an end. It occurred under the Act on 3 December 1920 on temporary organization of the administrative authorities of the second instance provinces in the area of former Kingdom of Galicia and Lodomeria with the Grand Duchy of Cracow. The Tarnopol province was classified as a southern province and it was included in the so-called borderland provinces.The Tarnopol province, due to its location and its social structure, played an important role in the political plans of the ruling government in the Second Republic. That is why it was important who pursued this policy in the region, who was the provincial governor at the time. He was not only a representative of the Government in the province, but he also headed the territorial administration in a subordinate province.There were eight provincial governors in the interwar period: Karol Olpiński, Lucjan Zawistowski, Mikołaj Kwaśniewski, Kazimierz Moszyński, Artur Maruszewski, Kazimierz Gintowt-Dziewiałtowski, Alfred Biłyk and Tomasz Malicki. All of them also completed higher education mostly legal and performed military service. They also took other positions in the local administration before and knew the terrain on which they ruled.It proves that the selection of people for this position was not accidental and it proves as well that management of the Tarnopol province was a very important matter for the authorities in Warsaw.
Keywords: administracja; II Rzeczpospolita; minister spraw wewnętrznych; Tarnopol; Prowincja Tarnopol